2019
DOI: 10.1097/sla.0000000000003284
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Response, Perioperative Outcomes, and Survival Following Total Neoadjuvant Therapy for Borderline/Locally Advanced Pancreatic Cancer

Abstract: Objective: To identify predictive factors associated with operative morbidity, mortality, and survival outcomes in patients with borderline resectable (BR) or locally advanced (LA) pancreatic ductal adenocarcinoma (PDAC) undergoing total neoadjuvant therapy (TNT). Background: The optimal preoperative treatment sequencing for BR/LA PDA is unknown. TNT, or systemic chemotherapy followed by chemoradiation (CRT), addresses both occult metastases and positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
280
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(365 citation statements)
references
References 49 publications
27
280
1
5
Order By: Relevance
“…Regarding survival rates, a Japanese monocentric comparative study including 375 patients, including 142 classified as "borderline resectable" who underwent upfront resection, showed that the rate of R0 resections was lower in case of VR (n = 91) (69 vs. 77%) including when preoperative CT scan demonstrated unilateral venous contact (Nakao Type B) (77). Moreover, the N+ rate was higher (80 vs. 65%) and the prognosis was poorer than that in patients with "clearly" resectable tumors (median cancer-specific survival: 14.4 vs. 24.4 months and median recurrence-free survival: 12 vs. 16.5 months; p = 0.0038). Survival was correlated with the severity of venous involvement observed on preoperative CT scan (Nakao Types B, C, or D: median specific survival 26, 12, and 16 months, respectively).…”
Section: Impact Of the Reconstruction Technique On The Long-term Permmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding survival rates, a Japanese monocentric comparative study including 375 patients, including 142 classified as "borderline resectable" who underwent upfront resection, showed that the rate of R0 resections was lower in case of VR (n = 91) (69 vs. 77%) including when preoperative CT scan demonstrated unilateral venous contact (Nakao Type B) (77). Moreover, the N+ rate was higher (80 vs. 65%) and the prognosis was poorer than that in patients with "clearly" resectable tumors (median cancer-specific survival: 14.4 vs. 24.4 months and median recurrence-free survival: 12 vs. 16.5 months; p = 0.0038). Survival was correlated with the severity of venous involvement observed on preoperative CT scan (Nakao Types B, C, or D: median specific survival 26, 12, and 16 months, respectively).…”
Section: Impact Of the Reconstruction Technique On The Long-term Permmentioning
confidence: 99%
“…Both the Mayo Clinic group (24,120) and Bachellier et al (121) reported more than 100 ARs (LE 4). In 2018, the Mayo Clinic group reported results in 111 patients who underwent pancreatectomy with AR [HA (n = 60), celiac (n = 49), SMA (n = 15), multiple ARs (n = 15)] including 55% with reconstruction and 51% with simultaneous VRs (120).…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study by Truty and colleagues, among 194 patients with BR or LAPC PDAC treated with "total neoadjuvant therapy" with FOLFIRINOX or GA, 28% had radiographic downstaging (37). A similar rate of radiographic downstaging, strikingly higher than that reported in the past, maybe due to a higher efficacy of modern chemotherapy regimens, but it may also simply reflect artifact of study conduct (such as, in this case, the exclusion of patients who did not undergo surgery).…”
Section: Radiographic Responsementioning
confidence: 99%
“…In 2017, a study from MD Anderson showed that baseline factors including young age, pretreatment CA 19-9 level, and use of gemcitabine as a radio-sensitizer were associated with pMR. Two other studies correlated positron emission tomography (PET) complete metabolic response and CA 19-9 response to pCR (37,52,53).…”
Section: Pathologic Responsementioning
confidence: 99%